Borrower income and loan rates in the credit market of Lima. Issue 2 (4th May 2022) - Zegarra, Luis Felipe
ABSTRACT: I analyse the effect of borrower income on loan rates in the credit market of Lima in 1840–65. I show that borrower income had a negative effect on interest rates. Borrower income influenced interest rates mostly through the impact on loan sizes: richer borrowers received larger loans and larger loans were associated with lower loan rates. The results are consistent with the influence of economies of scale on lending and differences in risk between large and small borrowers.